PERLINDUNGAN HUKUM BAGI GURU SEBAGAI TENAGA PROFESIONAL BERBASIS NILAI KEADILAN - Budoyo, Sapto (Jurnal Meta-Yuridis, 2022)
The rise of various cases that befell teachers in carrying out their professional duties is proof that legal protection for the teaching profession has not been running properly. This study consists of 3 (three) main problems, including legal protection for teachers as professionals, the weaknesses of legal protection for teachers as professionals, and efforts to realize legal protection for teachers as professionals based on the value of justice. This study uses a normative legal method by using a literature study. The results of this study state that the legal protection of the teaching profession as a professional educator is currently regulated in Law no. 20 of 2003 concerning the National Education System and Law no. 14 of 2005 concerning Teachers and Lecturers. Weaknesses in the legal protection of teachers as professionals, namely the teaching profession do not yet have the right not to be prosecuted in carrying out their professional duties and many cases go to the police (criminal), civil courts, and even state administrative courts. Efforts to realize the protection of teachers as professionals based on the value of justice through the reconstruction of articles 39 and 44 of Law no. 14 of 2005 concerning Teachers and Lecturers relating to the principle that teachers cannot be prosecuted either civilly, administratively, or criminally in carrying out their professional duties in good faith and or pedagogical principles for the benefit of education in the learning process.Â